STRATEGI PENGEMBANGAN EKOWISATA MANGROVE DESA BULU CINDEA KABUPATEN PANGKEP SULAWESI SELATAN - Rajab, Muhammad Arhan; Nurdin, Nurdin; Khumaera, Nur Ifra (Sam Ratulangi University, 2022)
The purpose of this research is to formulate a strategy for developing mangrove ecotourism in Bulu Cindea Village, Maros Regency. The sampling method used in this research is the accidental sampling method. Interviews were conducted on 37 visitors or tourists. Data analysis was carried out using the SWOT method with descriptive qualitative and quantitative descriptive, the results of the identification of potential natural resources in the form of flora and fauna were described to find out tourist attraction objects that could be developed. In analyzing visitor perception data, the analysis used is by using a Likert scale. Based on the results of the SWOT analysis, the strength factors include, the type of mangrove ecosystem, has beauty, attractiveness in the form of mangrove species and attractiveness in the form of a wooden bridge (log track) and the opportunity factor where the high motivation of visitors to enjoy the sunset on mangrove ecotourism, the high motivation of the end to walk the bridge wood, high visitor motivation to see mangroves and accessibility in the form of asphalt roads to mangrove ecotourism areas.